The influence of the trend of urban growth of city of Novi Sad on air quality in parks - Cavic Aleksandra M. (Proceedings of the International Symposium on Analytical and Environmental Problems, 2023)
Quality control of air in urban green areas - urban parks are rarely studied spaces, and this paper is based on research on the effects and impacts of microclimatic parameters on the detected suspended particles (PM 2.5 and PM10) with a multidisciplinary influence on public health and the quality of life of Novi Sad citizens. Excessive urbanization of urban environments and global migrations are among the most important causes of increased concentrations of air pollutants, even in urban green areas such as parks. This scientific research is part of a project focused on the effects and discrepancies of microclimatic parameters on detected concentrations of total suspended particles in the city's green parks in Novi Sad. Three urban parks of different sizes and locations with varying microclimatic influences were selected. Measurements of suspended particles (PM) were conducted at Futoški Park (FP), Dunavski Park (DP), and Limanski Park (LP) using a mobile device Aeroqual Series 500. At each location (FP, DP, LP), 10 measurements of suspended particle concentrations were conducted, with the device reporting changes in detected particle concentrations in real time. The results of the measured concentrations of suspended particles indicate variations in detected particle concentrations, with PM2.5 ranging from 4 to 36.1 μg/m3, while PM10 was detected in the range of 7 to 40.1 μg/m3. The measurement period for suspended particle pollution ranged from 12:00 to 17:30, with measured temperature fluctuations from 24.1 to 30.0°C and measured relative humidity oscillating between 39.1% and 54.4%.